Association of disease knowledge and medication adherence among out-patients with Type 2 Diabetes Mellitus in Khobar, Saudi Arabia - AlShayban, Dhfer Mahdi; Naqvi, Atta Abbas; Alhumaid, Othman; AlQahtani, Ali Saad; Islam, Md. Ashraful; Ghori, Syed Azizullah; Haseeb, Abdul; Ali, Majid; Iqbal, Muhammad Shahid; Elrggal, Mahmoud E.; Ishaqui, Azfar Athar; Mahmoud, Mansour Adam; et al. (Frontiers Media S.A., 2020)
Objective: The study aimed to evaluate the association between disease knowledge and medication adherence in patients with type 2 diabetes mellitus. Methods: A cross-sectional study was conducted for three months, in patients with type 2 diabetes who visited three community pharmacies located in Khobar, Saudi Arabia. Patients’ disease knowledge and their adherence to medications were documented using Arabic versions of the Michigan Diabetes Knowledge Test and the General Medication Adherence Scale respectively. Data were analyzed through SPSS version 23. Chi-square test was used to report association of demographics with adherence. Spearman’s rank correlation was employed to report the relationship among HbA1c values, disease knowledge and adherence. Logistic regression model was utilized to report the determinants of medication adherence and their corresponding adjusted odds ratio. Study was approved by concerned ethical committee (IRB-UGS-2019-05-001). Results: A total of 318 patients consented to participate in the study. Mean HbA1c value was 8.1%. A third of patients (N = 105, 33%) had high adherence and half of patients (N = 162, 50.9%) had disease knowledge between 51% - 75%. A significantly weak-to-moderate and positive correlation (ρ = 0.221, p < 0.01) between medication adherence and disease knowledge was reported. Patients with >50% correct answers in the diabetes knowledge test questionnaire were more likely to be adherent to their medications (AOR 4.46, p < 0.01). Conclusion: Disease knowledge in most patients was average and half of patients had high-to-good adherence. Patients with better knowledge were 4 to 5 times more likely to have high adherence. This highlights the importance of patient education and awareness regarding medication adherence in managing diabetes. © Copyright © 2020 AlShayban, Naqvi, Alhumaid, AlQahtani, Islam, Ghori, Haseeb, Ali, Iqbal, Elrggal, Ishaqui, Mahmoud, Khan and Jamshed.